Biochar filler in MEX and VPP additive manufacturing: characterization and reinforcement effects in polylactic acid and standard grade resin matrices - Nectarios Vidakis; Dimitrios Kalderis; Markos Petousis; Emmanuel Maravelakis; Nikolaos Mountakis; Nikolaos Bolanakis; Vassilis Papadakis (Biochar, 2023)
Abstract The development of sustainable and functional biocomposites remains a robust research and industrial claim. Herein, the efficiency of using eco-friendly biochar as reinforcement in Additive Manufacturing (AM) was investigated. Two AM technologies were applied, i.e., vat photopolymerization (VPP) and material extrusion (MEX). A standard-grade resin in VPP and the also eco-friendly biodegradable Polylactic Acid (PLA) in the MEX process were selected as polymeric matrices. Biochar was prepared in the study from olive trees. Composites were developed for both 3D printing processes at different biochar loadings. Samples were 3D-printed and mechanically tested after international test standards. Thermogravimetric Analysis and Raman revealed the thermal and structural characteristics of the composites. Morphological and fractographic features were derived, among others, with Scanning Electron Microscopy (SEM) and Atomic Force Microscopy (AFM). Biochar was proven to be sufficient reinforcement agent, especially in the filament MEX process, reaching more than 20% improvement at 4 wt.% loading in tensile strength compared to the pure PLA control samples. In the VPP process, results were not as satisfactory, still, a 5% improvement was achieved in the flexural strength with 0.5 wt.% biochar loading. The findings prove the strong potential of biochar-based composites in AM applications, too. Graphical Abstract